2010
DOI: 10.1080/17441690902942498
|View full text |Cite
|
Sign up to set email alerts
|

The motivations for participation in public–private partnerships for the provision of tuberculosis treatment in South Africa

Abstract: There is increasing interest in public-private partnerships (PPPs) generally, and more specifically for the provision of tuberculosis (TB) treatment, yet little is known about the motivations for such partnerships and the nature of the incentives that are required to achieve a desirable outcome of the partnerships. Using the new institutional economics approach, this study examines the motivations for participation in existing and potential models of PPPs for the provision of TB treatment in South Africa. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 10 publications
0
33
0
3
Order By: Relevance
“…PPM is cost‐effective in diverse country settings (Floyd et al. 2006; Sinanovic & Kumaranayake 2006; Pantoja et al. 2009; Mahendradhata et al.…”
Section: Discussionmentioning
confidence: 99%
“…PPM is cost‐effective in diverse country settings (Floyd et al. 2006; Sinanovic & Kumaranayake 2006; Pantoja et al. 2009; Mahendradhata et al.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Indonesia found that a substantial proportion of TB patients cared for at PPM DOTS hospitals are not managed under the DOTS strategy 65 . It is perhaps necessary to monitor the quality of care provided by the partnership 66 with attention to underlying motivations 67 …”
Section: Preventive Strategiesmentioning
confidence: 99%
“…65 It is perhaps necessary to monitor the quality of care provided by the partnership 66 with attention to underlying motivations. 67…”
Section: Preventive Strategiesmentioning
confidence: 99%
“…Further, the cost-effectiveness studies examining PPM for TB control do not compare different PPM strategies, but focus on the cost-effectiveness compared with current practice in the public or private sector [6,10], or simply estimate a cost-effectiveness ratio [8,16].…”
Section: Introductionmentioning
confidence: 99%